THE IMPACT OF LEARNER-CENTERED APPROACH ON EFL LEARNERS’ WRITING SKILL - DEWALI, TAYBAT IZAT (Journal of Duhok University, 2023)
Contemporary education calls for the use of learner-centered approach over the traditional education where students are passive learners. English as a foreign language can be best learned in a learner-centered approach. The writing skill has always been taught in a teacher centered approach in schools which made students graduate with poor writing skills. Therefore, researchers recommend the use of the learner-centered approach to develop the writing skill of language learners. For this reason, a new educational system called the Bologna Process which adopts a learner-centered approach is currently being implemented in some departments and colleges of the University of Duhok. This study investigates the effectiveness of the learner-centered approach in the learners’ writing skill, learner’s attitudes towards learning academic writing in a learner-centered teaching and learning environment, and to find out which learner-centered based activity students mostly prefer adopt when learning academic writing. For this purpose, 16 students from the English Language Department/ College of Basic Education have been interviewed. The results show that students find the learner-centered approach to have a positive effect on their writing skill since it help enhance their knowledge, grammar, vocabulary, spelling, punctuation, brainstorming activities and essay structure. As result, they have developed a positive attitude towards this approach and want to continue learning academic writing. The findings also have revealed that the most preferred learner-centered activities are students’ presentations and group work. Finally, the study ends up with some conclusions and recommendations